Long-term oxygen therapy to reduce length of hospital stay in COVID-19 - da Silva, Douglas Inomata Cardoso [UNESP]; Ishimoto, Letícia Yumi [UNESP]; Franco, Estefânia Aparecida Thomé [UNESP]; dos Santos, Maércio Souza Cícero [UNESP]; Brizola, Luís Fernando Pereira [UNESP]; Colombo, Camila Aparecida [UNESP]; Savadkouhi, Edris Guardiano [UNESP]; Machado, Luiz Henrique Soares [UNESP]; Tanni, Suzana Erico [UNESP]; Prudente, Robson [UNESP] (FapUNIFESP (SciELO), 2024)
OBJECTIVE: The aim of this study was to evaluate the efficacy of long-term oxygen therapy as a strategy to reduce hospitalization time in patients affected by COVID-19. METHODS: Between April and December 2021, COVID-19 patients with stable clinical conditions needing supplementary oxygen therapy during hospitalization were oriented to have hospital discharge with long-term oxygen therapy and reassessment after 15 days. RESULTS: A total of 62 patients were evaluated and, 15 days after discharge, 69% of patients had suspended long-term oxygen therapy, with no difference between the groups admitted to the intensive care unit or the ward (p=0.319). Among the individuals who needed to maintain long-term oxygen therapy, in addition to worse P/F ratio (265±57 vs. 345±51; p<0.001) and lower partial pressure of oxygen (55±12 vs. 72±11 mmHg; p<0.001), were those more obese (37±8 vs. 30±6 kg/m2; p=0.032), needed more time for invasive mechanical ventilation (46±27 vs. 20±16 days; p=0.029), had greater persistence of symptoms (p<0.001), and shorter time between the onset of symptoms and the need for hospitalization (7 [2–9] vs. 10 [6–12] days; p=0.039). CONCLUSION: Long-term oxygen therapy is an effective strategy for reducing hospitalization time in COVID-19 patients, regardless of gravity. Additionally, more obese patients with persistence of respiratory symptoms, faster disease evolution, and more days of invasive mechanical ventilation needed to maintain the long-term oxygen therapy longer.
Keywords: COVID-19; Hospitalization; Hypoxemia; Oxygen inhalation therapy; SARS-CoV-2